The diabetes gene Tcf7l2 organizes gene expression in the liver and regulates amino acid metabolism - Joanna Krawczyk; William O’Connor; Pedro Vendramini; Mareike Schell; Kiran J. Biddinger; Matt Kanke; George Pengo; Ivana Semova; Tiffany Fougeray; Marcia Haigis; Krishna G. Aragam; Wouter H. Lamers; et al. (Molecular Metabolism, 2025)
Objective: Though Tcf7l2 harbors the strongest genetic association with diabetes identified thus far, how it promotes metabolic disease remains unclear. Our aim was to dissect the contribution of hepatic TCF7L2. Methods: Mice with liver-specific knockout of Tcf7l2 produced by targeted deletion of exon 1 were subjected to physiological characterization, single nucleus sequencing, and metabolite profiling. In parallel, a phenome-wide association study was performed in humans. Results: We found that liver-specific deletion of Tcf7l2 had little effect on plasma glucose, but disrupted hepatic zonation. That is, many genes normally show gradients of expression across the liver lobule; in the absence of Tcf7l2, these gradients collapsed. One major consequence was the disorganization of glutamine metabolism, with a loss of the glutamine production program, ectopic expression of the glutamine consumption program, and a decrease in glutamine levels. In parallel, glutamine was found to be the most significantly decreased metabolite in the plasma of individuals harboring the rs7903146 variant in Tcf7l2. Conclusions: Taken together, these data indicate that hepatic TCF7L2 has a secondary role in glycemic control, but a primary role in maintaining transcriptional architecture and glutamine homeostasis.